Attitudes toward Mother Tongue and Academic Performance: Evidence from Monolingual Context in the Southern Philippines - Michael B. Cahapay (International Journal of Language Teaching and Education, 2020)
The influence of language attitude on the academic achievement of young children in the monolingual context has not been explored. Thus, this research ascertained the degree of relationship between attitudes toward the mother tongue and the academic performance of the learners. It entailed correlation research design. The respondents were 20 Grade II pupils in a rural public school considered as monolingual in the southern Philippines. The data gathered were treated using frequency distribution, weighted mean, percentage rate, and Pearson Product Moment Correlation Coefficient. It was found out that there is a significant relationship between attitudes toward the mother tongue and the academic performance of learners. Amid the vast body of diverse researches in the area of language education, the present study weaves pieces of evidence that attitudes of learners toward mother tongue are associated with their academic performance in the context of a monolingual environment. It is suggested that such a conclusion should be further tested in other contexts.